Evaluation of polyurethane sponge biocarrier effects on Litopenaeus vannamei cultivation in zero water exchange systems based on water quality, shrimp performance and bacterial community analysis - Liu, Chao; Chen, Liguo; Xu, Ailing; Song, Zhiwen (Frontiers in Environmental Science, 2023)
To evaluate the effects of polyurethane sponge biocarriers with precultured biofilms (PSBF) on water quality, shrimp performance and bacterial communities, zero water exchange systems for Litopenaeus vannamei were constructed. The experiment consisted of four treatments: 1) NBF (control, PSB (polyurethane sponge biocarriers) 5% (v/v) + aeration); 2) PSBF2.5a (PSBF 2.5% (v/v) + aeration); 3) PSBF5a (PSBF 5% (v/v) + aeration); and 4) PSBF5 (PSBF 5% (v/v)). The results showed that the systems with PSBFs had low levels of NH4+-N, NO2−-N, and turbidity, and there was zero water exchange throughout the entire culture process. The mean final weight, survival rate and final biomass of Litopenaeus vannamei in the PSBFs treatments were significantly higher, while the feed conversion ratio was lower than in the NBF treatments. The high-throughput sequencing results showed that the bacterial community abundance and diversity of biofilms in the PSBF systems were higher than those in the NBF systems. Four main genera of bacteria related to nitrification, Nitrosococcus, Nitrosomonas, Nitrococcus and Nitrospira, were identified. The total relative abundances of Nitrospira and Nitrosomonas in the PSBF systems were significantly higher than those in the NBF system. Meanwhile, better removal effects of NH4+-N and NO2−-N could be achieved and were positively correlated with the abundances of nitrifying microbial communities in PSBs, further indicating that nitrifying microbial communities in PSBs had positive effects on water quality and shrimp productive performance. This study provides data to support the application of polyurethane sponge biocarriers with precultured biofilms in zero water exchange systems for L. vannamei culture.